The Push to Publish: What is the Impetus for Australian Academic Librarians?. Issue 4 (8th November 2017) - Charing, Sarah; Gardiner, Blair
Abstract: Drawing on a case study about a librarian/academic research and writing collaboration, this paper proposes why, despite a lack of explicit compulsion, academic librarians in Australia should choose to research and write for publication. It offers a reflection on the process as seen through the authors' experience of a collaboration between academic librarians and a faculty academic, and considers the challenges and benefits in establishing a publishing track record. It argues that there are benefits in collaborative research for librarians with academics in generating research and publishing it to contribute to evidence-based practice, individual professional development and to contribute to their organisation's publication output.